Transient Neonatal Diabetes Associated with Chromosome 6Q24 Imprinting Abnormalities. Part 3. Clinical Picture and Diagnostics - O.Ye. Abaturov; L.L. Petrenko; O.O. Yermolaieva; V.A. Yenhovatova; I.A. Uzilevska (Zaslavsky O.Yu., 2016)
The paper presents the characteristics of clinical periods of 6q24-TNDM development: neonatal hyperglycemia, remission and type 2 diabetes mellitus. We present the clinical features of 6q24-TNDM depending on genetic disorders. The article indicated the clinical and laboratory criteria for 6q24-TNDM diagnosis. The methods of modern molecular and genetic diagnosis and the limitations of prenatal diagnosis were described in detail.